Sikap Siswa Terhadap Penerapan Media Visual Gambar Hubungannya Dengan Minat Belajar Siswa - Salsabila Firdausiyah (UIN Sunan Gunung Djati Bandung, 2022)
This research is motivated by the lack of interest in student learning in the subjects of Islamic Religious Education and Character Education at SMPN 1 Jatinangor. The contributing factor is that students feel bored or bored with monotonous learning media, therefore teachers must be more creative in developing learning media to make it easier and more interesting that can involve students in learning. Therefore, the authors are interested in researching students' attitudes towards the application of visual media images in relation to the learning interest of class VII students in the subject of Islamic Religious Education and Budi Pekerti. The purpose of this study was to determine: (1) Knowing students' attitudes towards the application of visual media images in the subjects of Islamic Religious Education and Character Education at SMPN 1 Jatinangor, (2) Knowing students' interest in learning about the subjects of Islamic Religious Education and Character Education at SMPN 1 Jatinangor, (3) Knowing the extent of the relationship between students' attitudes towards the application of visual media images with the learning interest of class VII students in the subject of Islamic Religious Education and Character Education at SMPN 1 Jatinangor. This study uses quantitative research methods that use the type of correlational research. This method is used to determine the relationship between two variables by comparing the results of the measurements of the two variables. Meanwhile, the data collection techniques used were observation, interviews, questionnaires, and literature study. The results of this study indicate that: 1) The students' attitudes towards the application of visual media images are in the good category. Based on the average value of 3.59 which is in the interval 3.40-4.19. 2) Students' interest in learning in the subjects of Islamic Religious Education and Character in the high category. Based on the average value of 4.13 which is in the interval 3.40-4.19. 3) The relationship between variables X and Y (a) The correlation coefficient is in the low category with a correlation value of 0.27 which is in the interval 0.200-0.399. (b) The hypothesis is accepted, the more positive the student's attitude towards the application of visual media images, the higher the student's interest in learning in the subjects of Islamic Religious Education and Character Education. This is based on hypothesis testing, namely t_(count> ) t_table (2,009 > 0.279) and (c) The degree to which there is Variable X with Variable Y of 7.29% which means that there are 92.71% of other factors that influence interest in learning Islamic Religious Education and Character.